The Role of Amniotic Fluid as a Biomarker for Identifying and Evaluating Microplastic Exposure - Nabilatun Nasaroh; Dinda Auliyatus Saidah; Paksi Samudro (Environmental Pollution Journal, 2026)
Microplastics (MPs) are environmental contamination that can potentially threaten the health of pregnant women and fetuses. This study aims to identify the presence and characteristics of Microplastics (MPs) in amniotic fluid and evaluate their potential as biomarkers of exposure during pregnancy. The study used a cross-sectional observational approach with 14 amniotic fluid samples collected aseptically in Gresik Regency. Analysis was performed through biological digestion using KOH and identification of particles in the samples by microscopy. Results showed all samples contained MPs dominated by Fiber type. This finding confirms the ability of MPs to penetrate biological barriers and reach an environment that should be sterile for the fetus. This study confirms the importance of monitoring MPs exposure during pregnancy and recommends utilizing amniotic fluid as a biomarker to support prevention and mitigation strategies for maternal and fetal health risks.